A comparative study between ORC and Kalina based waste heat recovery cycles applied to a green compressed air energy storage (CAES) system. (15th October 2020) - Soltani, M.; Nabat, Mohammad Hossein; Razmi, Amir Reza; Dusseault, M.B.; Nathwani, Jatin
Highlights: Proposing an efficient and green compressed air energy storage system. Analyzing and comparing various waste heat recovery cycles combined with compressed air energy storage. Using working fluids with near zero environmental effects. Drawing detail temperature-entropy diagrams for all of the proposed systems. Improving the energy and exergy round trip efficiencies by 2.67 and 2.69% by applying the ORC-R290 cycle. Abstract: Intermittent nature of the generated power from renewable energy resources and a higher demand for electricity during peak demand periods have intensified the need for grid-scale energy storage systems. Compressed air energy storage system, owing to significant merits such as minimum geographical and environmental limits and high reliability, has attracted attention in recent years. To improve efficiency, its hybridization with various waste heat recovery cycles has been taken into the account. To provide the grid with further power during peak demand periods, organic Rankine and Kalina cycles are the most practical alternatives. Hence, the combination of a green compressed air energy storage with various low- and medium-temperature waste heat recovery cycles is analyzed in the present article to address the most feasible choice in diverse working conditions. The subcritical and supercritical organic Rankine cycles with different working fluids (R717, R1270, R290, and R1234yf), as well as two Kalina cycles (KCS11 and KCS34) are analyzed from the perspective of the first and second laws of thermodynamics and compared with each other. The results indicate that the energy and exergy round trip efficiencies can be improved by 1.69–2.67% and 1.70–2.69%, compared to the stand-alone compressed air energy storage. The supercritical organic Rankine cycle with R290 as the working fluid is the best alternative, which recovers the highest amount of wasted heat and improves the production capacity by 2.47%.